Analysis of e-Service quality performance at BKPSDM Lubuklinggau web-based using E-Govqual and Importance Perfomance Analysis (IPA) methods - Astuti, Tri Puja; Elmayati, Elmayati; Hasanah, Tri (Sinkron : jurnal dan penelitian teknik informatika, 2022)
The Agency for Personnel and Human Resources Development (BKPSDM) uses the E–Kinerja service system. E-performance is a system for measuring employee performance. E- Govqual is a method that has attributes for assessing service quality. E-Government Importance Performance Analysis (IPA) is an assessment analysis method to measure the quality of a service based on the level of importance and level of performance perceived by the user. The research was conducted with the concept of measuring service quality in the form of electronic services focused on a government website called E-Government Quality (E-Govqual). The results of the gap analysis at this stage are carried out to determine the level of gap or difference in expectations between user interests and perceived system performance or user perceptions of the service quality of the E-Kinerja system. In the analysis of the level of conformity, the measurement is carried out by calculating the comparison between the reality of the service perceived by the user and the expectation of the service that the user wants. Furthermore, the analysis process is carried out with Importance Performance Analysis (IPA) using quadrant analysis whose results are mapped into Cartesian with the importance and performance axes. Based on the final results, the calculation shows the average level of conformity of each indicator in the four E-Govqual variables. From the table, it can be seen that all the average values ​​of the suitability level of the 4 dimensions are 101%. These results indicate that the performance of each attribute in the E-Kinerja application can meet the expectations of users. Based on the final result of the variable calculation, the largest gap occurs in the Trust variable with an average value of 0.05, then the smallest gap is in the Reliability Variable with an average value of -0.05 variable.